Literature and Ageing - Gilleard, Chris; Barry, Elizabeth; Skagen, Margery Vibe (Age, Culture, Humanities: An Interdisciplinary Journal, 2021)
In the category “Review Response,” Age, Culture, Humanities features diverse, sometimes conflicting, views within age studies and assessments of the research carried out in the field. This article takes Elizabeth Barry’s and Margery Vibe Skagen’s 2020 anthology Literature and Ageing as a case in point to raise questions about some of the central tenets and approaches in the study of literature and aging. Most importantly, as the title suggests, the edited collection promises a clearer understanding of the relation between literature and ageing. In the first section, Chris Gilleard offers his thoughts on the anthology and its essays. He raises a number of critical questions that, so we (in our capacity as co- editors of Age, Culture, Humanities) felt, address issues that are not only relevant to the anthology but are of larger importance to the field of age studies: What can literary studies – with its different methods and theories – add to the study of age and aging? In order to enable a generative conversation about these questions, we invited the editors Barry and Skagen to write a response to Gilleard’s critique. It constitutes the second section of this article and, rather than defend their work, Barry and Skagen clarify what is, in their view, the role of literature in age studies.